The Role of Memory and Language in Transformation: Crucial Issues in American Indigenous Poetry - Bayu Kristianto (Soegijapranata Catholic University, 2019)
The integration of the personal and the political has been an engaging topic in analyses of literary texts by authors whose works are known for their political content and activism, as well as an emphasis on social justice. Literary audiences in the United States have been familiar with Joy Harjo and John Trudell, two well-known contemporary Indigenous poets, who have voiced out the concerns of Indigenous people in the face of colonization and injustice happening in their homeland. Within the fusion of the personal and the political, as well as the mythical, the idea of transformation is paramount for Indigenous authors since to move from the state of being colonized to one of being decolonized, transformation is undoubtedly crucial. This paper focuses on the role of memory and the power of language in the process of transformation in the three poems by Joy Harjo and John Trudell. The analysis uses a qualitative methodology in the form of a close reading of literary texts to uncover the interconnectedness of memory and language in transformation. I argue that Native poets experience personal transformation that is critically influenced by the role of ancestral memory and social and historical consciousness in the broader context of Indigenous people’s struggle and resistance, as well as the power of language to see reality differently and affect its change. The analysis is intended to show to what extent the concepts of memory and language are critical in the process of decolonization and the manners in which these texts can be empowering for both Indigenous and non-Indigenous audiences in response to forms of injustice through the integration of the personal, the political, and the mythical.